Faktor-Faktor mempengaruhi Nilai Perusahaan non-Keuangan yang tedaftar di Bursa Efek Indoensia - Marcella Marcella; Mungniyati Mungniyati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain empirical evidence about the effect of independent variables on firm value. This study uses a variable performance ratio, leverage ratio, profit sustainability ratio, shareholder's equity ratio, profitability, dividend payout ratio, firm size, firm productivity and firm age. The population used in this study were non-financial companies listed on the Indonesia Stock Exchange from 2015 to 2017. There were 118 non-financial companies selected to be used as the final sample and the hypothesis tested using multiple regression analysis This study shows that the performance ratio, dividend payout ratio, firm productivity and firm age have an influence on firm value, while the leverage ratio, profit sustainability ratio, shareholder's equity ratio, profitability, and firm size do not affect the firm's value.